Coenzyme Q10 for the Protection of Lacrimal Gland against High-Dose Radioiodine Therapy-Associated Oxidative Damage: Histopathologic and Tissue Cytokine Level Assessments in an Animal Model. (2nd December 2017) - Yakin, Mehmet; Eksioglu, Umit; Sadic, Murat; Koca, Gokhan; Ozkan-Uney, Guner; Yumusak, Nihat; Husniye Telek, Hande; Demir, Ayten; Yazihan, Nuray; Ornek, Firdevs; Korkmaz, Meliha
ABSTRACT: Purpose : To evaluate protective effect of coenzyme Q10 (CoQ10) in lacrimal glands against high-dose radioactive iodine (RAI)-associated oxidative damage. Materials and Methods : Thirty Wistar albino rats were randomly divided into three groups. Group 1 was the control group. Group 2 received 3 mCi/kg RAI via gastric gavage but no medication. Group 3 received 3 mCi/kg RAI via gastric gavage and 30 mg/kg/day CoQ10 intraperitoneally. CoQ10 was started at day one just before RAI administration and continued for five days. Seven days after RAI therapy, the animals were anesthetized and decapitated. Intraorbital (IG), extraorbital (EG), and Harderian (HG) lacrimal glands were removed bilaterally for histopathological and tissue cytokine level assessments. Results : Abnormal lobular pattern, acinar fibrosis, lipofuscin-like accumulations, perivascular infiltration, cell size variation, abnormal cell outlines, irregular nucleus shapes in all lacrimal gland types ( p < 0.05 for each), periductal fibrosis, periductal and periacinar fibrosis in EG ( p = 0.01, 0.044, respectively) and in HG ( p = 0.036, 0.044, respectively), periductal infiltration in HG ( p = 0.039) and IG ( p = 0.029), acinar atrophy in EG ( p = 0.044), and cell shape variation in IG ( p = 0.036) were observed more frequently in group 2 than in other groups. RAI caused significant increase in TNF-α, IL-6, nuclear factor kappa B, and total oxidant status, and decrease in IL-2, IL-10, and total antioxidant status levels ( p < 0.05 for each). Addition of CoQ10 decreased all cytokine levels, increased nuclear factor kappa B levels more, and increased total antioxidant status levels significantly ( p < 0.05 for each). Conclusions : RAI administration causes prominent inflammatory response in lacrimal glands. Addition of CoQ10 ameliorates the oxidative damage and protects lacrimal glands both in histopathological and tissue cytokine level assessments. Protection of lacrimal glands against oxidative damage may become a new era of CoQ10 use in the future.